CircRNAs in BALF exosomes and plasma as diagnostic biomarkers in patients with acute respiratory distress syndrome caused by severe pneumonia - Sun, He; Gao, Wei; Chen, Rongzhang; Chen, Si; Gu, Xia; Wang, Feilong; Li, Qiang (Frontiers in Cellular and Infection Microbiology, 2023)
Background: The transcriptomic studies targeting circular RNAs (circRNA) in bronchoalveolar lavage fluid (BALF) exosomes of acute respiratory distress syndrome (ARDS) patients caused by severe pneumonia have rarely been reported. This study aimed to screen and validate abnormally expressed circRNAs in exosomes from BALF of patients with ARDS caused by severe pneumonia, and then evaluate the diagnostic values of these circRNA for ARDS. Method: BALF was collected from four ARDS patients caused by severe pneumonia and four healthy subjects. CircRNAs expression profile was obtained by microarray analysis in BALF exosomes of discovery cohort. The differentially expressed circRNAs in BALF exosomes were verified by real-time quantitative PCR (RT-qPCR), and underwent competitive endogenous RNA (ceRNA) network construction and functional enrichment analysis. Results: Totally, 629 circRNAs were differentially expressed in BALF exosomes between ARDS patients and healthy subjects. Nine differentially expressed circRNAs were validated by RT-qPCR, and seven were consistent with the results of microarray analysis. CeRNA network analysis was performed for hsa_circRNA_002809, hsa_circRNA_042882 and hsa_circRNA_104034. Functional enrichment analysis showed that the target genes were mainly associated with hypoxia-induced damage, inflammatory response, and HIF-1 signaling pathway. Hsa_circRNA_042882 and hsa_circRNA_104034 can be regarded as promising diagnostic biomarkers for ARDS patients caused by severe pneumonia, with remarkable sensitivity and specificity of area under the curve of 0.8050 and 1 or 0.835 and 0.799, respectively. Conclusions: This study obtained circRNAs expression profile of ARDS patients, and hsa_circRNA_042882 and hsa_circRNA_104034 were regarded as promising diagnostic biomarkers for ARDS patients caused by severe pneumonia.